Differences in Academic Stress Based on Gender in Final Year Students of the Social Sciences Education Study Program at FKIP UNTAN - Roni, Roni; Aminuyati, Aminuyati; Karolina, Venny; Buwono, Sri; Wiyono, Hadi (Peneliti.net, 2024)
The aim of this research is to determine differences in academic stress among final year students of the Social Sciences Education study program based on gender at FKIP UNTAN Pontianak for the 2022/2023 period. The research design used is comparative. The total population was 61 students and the samples taken randomly using stratified random sampling were 22 male students and 31 female students. The instrument used was the student-life stress inventory (SSI) questionnaire which was packaged on the Google Form platform, the data was on a Likert scale, and used Independent t-test analysis. Data collection techniques were pilot tests, validity tests, reliability tests, questionnaire distribution, and the data were analyzed with the help of SPSS version 26. The research results showed that most students experienced low academic stress at 41.5%. The independent t-test obtained a sig value. (2-tailed) is 0.145 (p>0.05) so H0 is accepted, which means there is no difference in academic stress based on gender. This is due to the similarities in the causes of stress experienced and received by male and female final year students in the Social Sciences Education study program at FKIP UNTAN Pontianak for the 2022/2023 period. However, the data shows that the academic stress level of female students is higher (M=142.87) in the medium category than male students in the low category (M=131.59).